2022
DOI: 10.1111/ilr.12221
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and informal work: Evidence from 11 cities

Abstract: This article presents the findings for 11 cities across five geographical regions from a study led by Women in Informal Employment: Globalizing and Organizing, investigating the impacts of the COVID‐19 crisis on different groups of informal workers and their households. Detailing impacts on work and income, food and hunger, care and other household responsibilities, and on the coping strategies of informal worker households, the article also compares the roles of government and informal worker organizations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Poverty, which has not been substantially reduced in recent years, increased dramatically with the current health crisis, reaching 30.1%, which means an increase of 9.9% between 2019 and 2020 (11). In addition to these economic indicators, the Peruvian economy is characterized by its high informality, which reaches 69.2% (35). In relation to employment, a study conducted in the southern region of the country showed that 39% of households would have lost at least one job during the pandemic (36).…”
Section: Discussionmentioning
confidence: 99%
“…Poverty, which has not been substantially reduced in recent years, increased dramatically with the current health crisis, reaching 30.1%, which means an increase of 9.9% between 2019 and 2020 (11). In addition to these economic indicators, the Peruvian economy is characterized by its high informality, which reaches 69.2% (35). In relation to employment, a study conducted in the southern region of the country showed that 39% of households would have lost at least one job during the pandemic (36).…”
Section: Discussionmentioning
confidence: 99%
“…This pair of findings suggests that the impression of income stability has a crucial role in guiding the mitigation actions of workers and firms. In addition, informal labor is more likely to require a greater number of bailouts, such as credit aids, to maintain their living necessities and businesses' viability during times of financial hardship (Chen et al, 2022;ILO, 2020;Kumar, Mishra, Sonkar, & Saroj, 2020). The financial help can boost their output and increase their chances of survival in a generally economically susceptible sector (Brunnermeier & Krishnamurthy, 2020;Malik et al, 2020;Yue, Korkmaz, Yin, & Zhou, 2021).…”
Section: Financial Assetsmentioning
confidence: 99%
“…The lockdown measures taken across the world in March and April 2020 prevented most informal workers from leaving their homes to engage in paid work. Data from the global WIEGO-led study show that among the four sectors, home-based workers (who are predominantly women), somewhat ironically, were the least able to work and the slowest to recover as a result of a lack of jobs or work orders from employers and their contractors, and fluctuations in demand, supply, prices, and other factors in the supply chain (Chen et al 2022).…”
Section: Unpaid Care Work Informal Work and Crisesmentioning
confidence: 99%